His wicked charm [large type] - Camp, Candace (The mad Morelands, 2018)
Lilah Holcutt dislikes Constantine Moreland the moment she meets him. He may be handsome, but he's frivolous, rash, impulsive and a flirt. Now that Con's twin brother married Lilah's best friend, she sees way more of him than she'd like. And when Con's sisters are kidnapped, curiosity sweeps Lilah into his investigation. Con knows that Lilah hates him. He just wishes that he weren't so attracted to her . . . especially since they're working so closely together.